Dilemmas in providing resilience-enhancing social services to long-term social assistance clients. A qualitative study of Swedish social workers - Marttila Anneli; Johansson Eva; Whitehead Margaret; Burström Bo (BMC, 2012)
Abstract Background Long-term recipients of social assistance face barriers to social and economic inclusion, and have poorer health and more limited opportunities for improving their health than many other groups in the population. During recent decades there have been changes in Swedish social policy, with cutbacks in public benefits and a re-emphasis on means-tested policies. In this context, it is important to investigate the necessary conditions for social workers to offer social assistance and services, as well as the mediating role of social workers between public policies and their clients. Swedish social services aim to promote social inclusion by strengthening the individual´s own resources. We investigated the issues that arise when providing social services to long-term social assistance clients within the framework of resilience, which focuses on the processes leading to positive functioning in adverse conditions. Methods Interviews were conducted with 23 social workers in Stockholm and analysed by qualitative content analysis. Results The main theme to emerge from the interviews concerned the constraints that the social workers faced in providing social services to social assistance clients. The first subtheme focused on dilemmas in the interaction between social workers and clients resulting from the dual role of exercising authority and supporting and building trust with clients. Working conditions of social workers also played a crucial role. The second subtheme addressed the impact of the societal context, such as labour market opportunities and coordination between authorities. Conclusions Overall, we found that social workers to a great extent tried to find individual solutions to structural problems. To provide resilience-enhancing social services to long-term social assistance clients with varying obstacles and needs requires a constructive working environment, supportive societal structures and inter-sectoral cooperation between different authorities.